Artemisinin derivatives versus quinine for cerebral malaria in African children: a systematic review - Hmwe Hmwe Kyu; Eduardo Fernández (The World Health Organization, 2009)
OBJECTIVE: To summarize the existing evidence on the efficacy of artemether and arteether, two artemisinin derivatives, versus quinine for treating cerebral malaria in children. METHODS: We searched the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE and the http://clinicaltrials.gov web site. We also checked the reference lists of existing systematic reviews and of all trials identified by the above methods. We searched exclusively for randomized controlled trials (RCTs) comparing artemether/arteether with quinine for treating cerebral malaria in children. Two independent reviewers assessed study eligibility and trial quality and extracted the data. FINDINGS: Nine RCTs were included in the analysis, and all were from Africa. Five had adequate allocation concealment. Seven trials compared artemether with quinine (1220 children), and two compared arteether with quinine (194 children). No statistically significant difference was found between artemisinin derivatives and quinine in preventing mortality (relative risk, RR: 0.91; 95% confidence interval, CI: 0.73-1.14; I²: 0%). The quality of the evidence, as assessed by the Grade evidence profile, was moderate. The only serious adverse event was seen in a patient in the quinine group who developed fatal black water fever. CONCLUSION: Artemisinin derivatives are not inferior to quinine in preventing death in children with cerebral malaria.